HPV vaccination: acceptance and influencing factors among young men in Germany. (February 2016) - Schwarz, Theresa Maria; Honsberg, Thomas; Stephan, Nicolas; Dannecker, Christian; Gallwas, Julia; Crispin, Alexander; Weißenbacher, Ernst-Rainer; Kolben, Thomas
Aims: This study aims to determine the factors that influence the acceptance of the HPV vaccination among German males.Patient & methods: In 2014, we conducted a population-based cross-sectional study in men aged 15–25 years. A questionnaire was mailed to male trainees of the Bayerische Motorenwerke AG (BMW) insured at the BMW health insurance company.Results: The response rate was 10.8%. Of the 378 included men, 74.1% would agree to receive HPV vaccination. Most men primarily consult their physician for health-related topics, but 92.9% had never been informed about HPV infection, risk factors and prevention methods by their doctor.Conclusion: Our results demonstrate a high acceptance of male HPV vaccination. Education about HPV infection is low and should be intensified by medical professionals.